Evaluación del sistema islas flotantes artificiales (ifa) para la remoción de arsénico, a escala real en el reservorio del proyecto de riego Tiliche San José alto en el periodo 2021 – 2022. - Córdova Cunalata, Carlos Daniel (2022)
The volcanoes presence in Ecuador Andean zone has naturally contaminated water resources with heavy metals, generating a low quality of agricultural products and health problems. The objective of this research was to evaluate Artificial Floating capacity of Island System (AFIS) for arsenic removal at full scale in reservoir of Tiliche San José Alto Irrigation Project. The study was carried out in two stages: at first stage, species were adapted in the soil at 3089 m.o.s.l for root development; at second stage, eleven IFAs of 1 m2 with 50 vetiver and 29 achira plants were installed in the reservoir tank (162.53 m3) at an altitude of 3548 mosl. Subsequently, 15 water samples (4 for initial and 11 for final concentrations) were taken each 8 days for 4 months (132 days), recording values of pH, conductivity, temperature, phosphates, and arsenic and iron concentration; additionally, a sediment sample was taken to determine its concentration along the irrigation system. To determine the influence of the parameters (pH, E.C., temperature and phosphates) on contaminants concentration, Pearson's correlation coefficient was used. As speciation was performed by comparing the pH of water with speciation ranges, while for Fe it was performed according to climatic period of the study. The results indicated a removal of 26.9% As and 35.44% Fe. A direct correlation was established between As and Fe concentration with temperature and phosphate parameters, and an inverse correlation with E.C. Speciation of As and Fe showed a higher amount of As (V) than As (III), and more Fe (II) than Fe (III). It was concluded that the IFA System with vetiver Grass species (Crhysopogon zizanioides) - achira (Canna Indica), is a sustainable and low-cost eco-technological alternative for arsenic and iron removal from contaminated water sources, enabling its installation in areas with similar characteristics.